2015
DOI: 10.1007/s00396-015-3626-4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ni(II) ion on Ni(II) ion-imprinted magnetic chitosan/poly(vinyl alcohol) composite

Abstract: Magnetic chitosan/poly(vinyl alcohol)/Ni(II) beads (m-CTS/PVA/Ni(II)s) were prepared by blending CTS, PVA, Ni(II), and Fe 3 O 4 . Ni(II)-imprinted m-CTS/PVA beads (Ni(II)-IMCPs) were obtained by eluting Ni(II) ions from the m-CTS/PVA/Ni(II)s. The optimal conditions for preparing Ni(II)-IMCPs are 2.0 % (w/w) for CTS, 1.5 % (w/w) for PVA, 0.8 % (w/w) for Ni (NO 3 ) 2 , and 2.0 % (w/w) for Fe 3 O 4 . The Fourier transform infrared spectroscopy (FT-IR) analysis implies that the coordinating atoms may be N atom of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…19 To date, a lot of Ni(II) ion-imprinted polymers based on biomass have been prepared by surface imprinting technique for removal of nickel(II) from aqueous solution. [20][21][22][23][24] Silica gel has been widely applied as a support for surface imprinting materials due to its low cost, wonderful modication and excellent mechanical stability. 25 However, to our knowledge, there is only one literature on Ni(II) ion surfaceimprinted polymer based on silica gel functionalized with amino group for selective removal of Ni(II) from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…19 To date, a lot of Ni(II) ion-imprinted polymers based on biomass have been prepared by surface imprinting technique for removal of nickel(II) from aqueous solution. [20][21][22][23][24] Silica gel has been widely applied as a support for surface imprinting materials due to its low cost, wonderful modication and excellent mechanical stability. 25 However, to our knowledge, there is only one literature on Ni(II) ion surfaceimprinted polymer based on silica gel functionalized with amino group for selective removal of Ni(II) from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, its removal is highly demanded. Thus, several Ni(II)-imprinted materials have been prepared [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ] ( Table 4 ).…”
Section: Ion-imprinted Polymeric Materials For Selective Extraction O...mentioning
confidence: 99%
“…Magnetic CS/PVA beads, having improved adsorption capacity and selectivity for Ni(II) ions, have also been fabricated [ 103 ]. The maximum equilibrium adsorption capacity was reached within 6 h and the magnetic CS/PVA beads absorbed about 500 mg Ni(II)/g, at 298 K. In column experiments, the magnetic CS/PVA beads exhibited selectivity for Ni(II) recovery from multi-HMIs wastewater.…”
Section: Ion-imprinted Polymeric Materials For Selective Extraction O...mentioning
confidence: 99%
“…The removal of trace cobalt and other impurities from high purity nickel has become the key to improve the quality of high purity nickel. Zhang et al [21] have prepared a magnetic chitosan/poly(vinyl alcohol)/Ni(Ⅱ) beads by blending CTS, PVA, Ni(Ⅱ), and Fe 3 O 4 . Ni(II)-imprinted m-CTS/PVA beads (Ni(II)-IMCPs) were obtained by eluting Ni(II) ions from the m-CTS/PVA/Ni(II)s. The study on the adsorptive performances of Ni(II)-IMCPs showed that the process of adsorption is good fitted to Langmuir model and the maximum adsorption capacity of Ni(II)-IMCPs for Ni(II) ions is 500.00 [mg.g −1 ].…”
Section: Ni-iipsmentioning
confidence: 99%